Fiberglass Construction Testing Simulation On Boat Hulls - Febrian, Shahrin; Buwono, Ayom (Jurnal Sains & Teknologi Fakultas Teknik Universitas Darma Persada, 2024)
As a maritime country, Indonesia relies heavily on ships as an economical means of transportation and conveyance. Boats, which were used for many years, were originally made of wood. However, because wood has properties that are easily weathered due to weather and chemical factors and requires adequate maintenance, fiberglass material in the form of FRP (Fiber Reinforced Plastics) laminates appeared as a substitute for wood. This material has many advantages over wood, so ships made from FRP began to gain a place in the shipping world, especially among ship manufacturers. However, In 2009, a survey carried out at multiple shipyards revealed that the construction design and lamination process of fiberglass ship hulls generally did not have clear standards, resulting in a significant risk of accidents. To minimize this risk, a simulation of fiberglass construction testing was held with samples taken from 6 shipyards where each sample had a different configuration and material, and the results of Carbon Fiber provided optimal results.